2011
DOI: 10.1146/annurev-cellbio-092910-154237
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Glycolysis: Meeting the Metabolic Requirements of Cell Proliferation

Abstract: Warburg's observation that cancer cells exhibit a high rate of glycolysis even in the presence of oxygen (aerobic glycolysis) sparked debate over the role of glycolysis in normal and cancer cells. Although it has been established that defects in mitochondrial respiration are not the cause of cancer or aerobic glycolysis, the advantages of enhanced glycolysis in cancer remain controversial. Many cells ranging from microbes to lymphocytes use aerobic glycolysis during rapid proliferation, which suggests it may p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

49
2,372
2
22

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,536 publications
(2,445 citation statements)
references
References 155 publications
49
2,372
2
22
Order By: Relevance
“…We examined the expression of monocarboxylate transporters (MCT), which transport lactate across membranes 26 and found that among 7 MCTs, the MCT1 transcript was significantly induced by 0.1 Gy treatment ( Figure 2b). As lactate can be produced as the end product of glycolysis, 19,20 we measured glucose levels and detected an increase in glucose consumption induced by 0.1 Gy but not 4 Gy irradiation ( Figure 2c). Together with an elevated extracellular acidification rate (ECAR) in 0.1 Gy-treated cells, measured with a Seahorse XF Analyzer (Figure 2d), the results suggest an induction of glycolysis specific to low-dose IR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We examined the expression of monocarboxylate transporters (MCT), which transport lactate across membranes 26 and found that among 7 MCTs, the MCT1 transcript was significantly induced by 0.1 Gy treatment ( Figure 2b). As lactate can be produced as the end product of glycolysis, 19,20 we measured glucose levels and detected an increase in glucose consumption induced by 0.1 Gy but not 4 Gy irradiation ( Figure 2c). Together with an elevated extracellular acidification rate (ECAR) in 0.1 Gy-treated cells, measured with a Seahorse XF Analyzer (Figure 2d), the results suggest an induction of glycolysis specific to low-dose IR.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 0.1 Gy treatment of human fibroblasts also induced an increase in GLUT-1 and GLUT-3 at both the mRNA (Figure 2j) and the protein levels (Figure 2k), consistent with increased glucose flux. 20 The glycolytic switch is necessary for low-dose IRinduced resistance. The low-dose IR-induced glycolytic shift under normoxic conditions is similar to the 'Warburg effect', which has been shown to have an important role in promoting cancer cell proliferation and survival.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Activated T cells change their metabolic state by utilizing aerobic glycolysis. [41][42][43] The high rate of glycolysis in activated T cells bypasses the normal oxidation of pyruvate in the mitochondria, resulting in lactic acid fermentation, whereas minimal lactic acid production occurs in resting cells.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic transformation in cancer supports macromolecule biosynthesis and is crucial for cancer cell survival and tumour formation [1,2]. Many solid tumours exhibit increased glucose uptake and lactate secretion, a feature known as the Warburg effect.…”
Section: Introductionmentioning
confidence: 99%